2015
DOI: 10.1128/aac.03997-14
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Effect of 18β-Glycyrrhetinic Acid Is Mediated by Toll-Like Receptor-Dependent Canonical and Noncanonical p38 Activation

Abstract: b 18␤-Glycyrrhetinic acid (GRA), a natural immunomodulator, greatly reduced the parasite load in experimental visceral leishmaniasis through nitric oxide (NO) upregulation, proinflammatory cytokine expression, and NF-B activation. For the GRAmediated effect, the primary kinase responsible was found to be p38, and analysis of phosphorylation kinetics as well as studies with dominant-negative (DN) constructs revealed mitogen-activated protein kinase kinase 3 (MKK3) and MKK6 as the immediate upstream regulators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
(70 reference statements)
1
11
0
1
Order By: Relevance
“…Thus, it appears that the treatment effect of BKM120 on NSCLC cells with KRAS or even EGFR mutation is not completely known. Moreover, PD0325901 is one of the currently investigated MEK inhibitors, and is a synthetic organic molecule that selectively binds to and inhibits mitogenactivated protein kinase (MEK) (11). The RAS/MEK pathway plays an important role in cancer development and progression (7), and often demonstrates pathway convergence to the PI3K/Akt/mTOR pathway.…”
Section: Combined Use Of Pi3k and Mek Inhibitors Synergistically Inhimentioning
confidence: 99%
“…Thus, it appears that the treatment effect of BKM120 on NSCLC cells with KRAS or even EGFR mutation is not completely known. Moreover, PD0325901 is one of the currently investigated MEK inhibitors, and is a synthetic organic molecule that selectively binds to and inhibits mitogenactivated protein kinase (MEK) (11). The RAS/MEK pathway plays an important role in cancer development and progression (7), and often demonstrates pathway convergence to the PI3K/Akt/mTOR pathway.…”
Section: Combined Use Of Pi3k and Mek Inhibitors Synergistically Inhimentioning
confidence: 99%
“…Deeper analysis revealed that the MAPK (mitogenactivated protein kinase) p38 activation was dependent on GRA-mediated canonical and noncanonical activation where numerous upstream molecules play important roles [42]. This study further highlighted the importance of p38 MAPK (mitogen-activated protein kinase) in GRA-mediated parasite elimination and its activation by upstream kinases like MKK3/6 which itself is dependent upon upstream signaling molecules (Figure 6).…”
Section: Downregulation Of Toll-like Receptor (Tlr) Pathwaysmentioning
confidence: 81%
“…However, as another group of important cells during EAE, the activation of macrophage wasn’t affected by GRA. GRA can affect cell functions by targeting gap junction channels 33 34 , toll-kike receptor 35 , cytochrome P450 2E1(CYP2E1) 36 and so on. It has be regarded that these signalings such as gap junction channels paly critical roles in both microglia macrophages 37 .…”
Section: Discussionmentioning
confidence: 99%